Solar off-grid markets in Africa: Recent dynamics and the role of branded products - Michael Grimm; Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
Solar off -grid technologies have become a lower-cost alternative to grid-based electrification in rural Africa. As a contribution to the United Nations' electricity for all goals, policy currently promotes branded solar products based on the assumption that high-quality standards are necessary. We provide evidence suggesting that nonbranded technologies have already made widespread inroads to rural households. Quality is not necessarily worse, in particular if the considerably lower end-user prices are accounted for. A justification of branded solar promotion programs can thus not only be based on energy access arguments, but rather on environmental concerns related to electronic waste. Moreover, we show that if poorer strata are to be reached, end-user subsidies are required.
Keywords: O13; O33; Q41; 330; rural electrification; energy access; energy poverty; technology adoption